1997
DOI: 10.1023/a:1008291825695
|View full text |Cite
|
Sign up to set email alerts
|

Improved quality of life with megestrol acetate in patients with endocrine-insensitive advanced cancer: A randomised placebo-controlled trial

Abstract: Megestrol acetate given at 480 mg/day is useful palliation in patients with endocrine-insensitive advanced cancer. It improves appetite, mood and overall quality of life in these patients, although not through a direct effect on nutritional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 11 publications
0
43
0
2
Order By: Relevance
“…Synthetic progestagens, MA and MPA, are currently the only approved drugs for CACS in Europe; their mechanism of action may be partly related to glucocorticoid activity and the ability to downregulate the synthesis of proinflammatory cytokines [40] and to increase food intake by neuropeptide Y release [41]. To date, Ͼ15 randomized, controlled studies in weight-losing cancer patients have demonstrated that MPA and MA significantly improve appetite, food intake, body weight, and sometimes nausea and emesis, whereas in most trials, no definite improvement in global QoL was observed [42][43][44][45][46]. The weight gain observed with progestagens consists mainly of water and fat mass [47], having virtually no influence on LBM and functional activity [48].…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic progestagens, MA and MPA, are currently the only approved drugs for CACS in Europe; their mechanism of action may be partly related to glucocorticoid activity and the ability to downregulate the synthesis of proinflammatory cytokines [40] and to increase food intake by neuropeptide Y release [41]. To date, Ͼ15 randomized, controlled studies in weight-losing cancer patients have demonstrated that MPA and MA significantly improve appetite, food intake, body weight, and sometimes nausea and emesis, whereas in most trials, no definite improvement in global QoL was observed [42][43][44][45][46]. The weight gain observed with progestagens consists mainly of water and fat mass [47], having virtually no influence on LBM and functional activity [48].…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic progestogens, MA/MPA, are currently the only approved drugs for CACS in Europe. Several randomized studies in mixed groups of weight-losing patients with cancer have suggested that MA/ MPA improves appetite and stabilizes weight to an extent greater than placebo [4,[46][47][48][49]. The ω-3 polyunsaturated fatty acids (EPA and docosahexaenoic acid) have been shown to inhibit the production of proinflammatory cytokines and thereby to act positively on cancer cachexia.…”
Section: Combined Approachmentioning
confidence: 99%
“…Several randomized studies in mixed groups of weight-losing patients with cancer have suggested that MA/ MPA improves appetite and stabilizes weight to an extent greater than placebo. [44649] The ω-3 polyunsaturated fatty acids (EPA and docosahexaenoic acid) have been shown to inhibit the production of proinflammatory cytokines and thereby to act positively on cancer cachexia. In experimental tumor models, EPA has demonstrated antitumor and anticachectic effects.…”
Section: Introductionmentioning
confidence: 99%